Synthesis of Fluorescent Carbon Dots as Selective and Sensitive Probes for Cupric Ions and Cell Imaging - Huang, Shu-Wei (Molecules, 2019)
A novel sensing system has been designed for the detection of cupric ions. It is based on the quenched fluorescence signal of carbon dots (CDs), which were carbonized from poly(vinylpyrrolidone) (PVP) and L-Cysteine (CYS). Cupric ions interact with the nitrogen and sulfur atoms on surface of the CDs to form an absorbed complex; this results in strong quenching of the fluorescence of the CDs via a fast metal-to-ligand binding affinity. The synthesized water-soluble CDs also exhibited a quantum yield of 7.6%, with favorable photoluminescent properties and good photostability. The fluorescence intensity of the CDs was very stable in high ionic strength (up to 1.0 M NaCl) and over a wide range of pH levels (2.0–12.0). This facile method can therefore develop a sensor that offers reliable, fast, and selective detection of cupric ions with a detection limit down to 0.15 μM and a linear range from 0.5 to 7.0 μM (R(2) = 0.980). The CDs were used for cell imaging, observed that they were low toxicity to Tramp C1 cells and exhibited blue and green and red fluorescence under a fluorescence microscope. In summary, the CDs exhibited excellent fluorescence properties, and could be applied to the selective and sensitive detection of cupric ion and multicolor cell imaging.